The Socialization of The Revocation of E-Warong In The BPNT Program In Sumberlesung Village, Ledokombo District, Jember Regency - Wijaya, Bayu; Rahmawati, Atik; Mubarok, Akhmad Munif (JAROW: Journal of Ar-Raniry on Social Work, 2025)
This study was conducted to determine the stages and impacts of the socialization of the revocation of E-Warong in the BPNT assistance program. The Ministry of Social Affairs issued a decree on February 24, 2023 containing socialization of regulations and prohibitions on disbursing assistance at E-Warong agents. However, in reality there are still many (KPM) who disburse assistance at E-Warong. one of them is in Sumberlesung Village, Ledokombo District, Jember Regency. The purpose of this study is to explain and describe the stages and impacts of the socialization of the revocation of E-Warong on the BPNT program. Qualitative research approach, descriptive research type. Determination of purposive area location. The technique of determining purposive sampling informants with one main informant and 9 additional informants. Observation data collection techniques, semi-structured interviews, documentation. Data analysis techniques include condensing data, displaying data, and drawing conclusions. The data validity technique uses the source triangulation technique. The results of this study indicate that with the socialization carried out by E-Warong agents and KPM, there were positive and negative impacts and the distribution of assistance was disbursed again at E-Warong.